A COMPARATIVE STUDY OF LEXICAL UNITS RELATED TO MOURNING IN UZBEK AND GERMAN LANGUAGES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article, the ceremonies and traditions of each nation have common and unique national and mental characteristics, they are connected with the history, culture, way of life and social changes of these nations, in the Uzbek and German nations While it is characteristic for both nations that the ceremonies related to wedding and funeral ceremonies occupy a large place in the structure of customs, they have certain customs according to the order and nature of the ceremonies. differences were observed.